Emphasis on heat strain to the ocular surface: A functional and clinical study of a modified goggle - Shao, Yuting; Wu, Jingzhong; Wu, Peichen; Liu, Xin; Shen, Jiaqi; Zhang, Li; Bi, Yanlong (Frontiers in Public Health, 2022)
Purpose The limitations of conventional goggles have caused immense inconvenience, and even damage, to the physical and mental health of healthcare workers. Hence, this study aimed to build a modified goggle (MG) with better physical performance. The temperature-humidity index (THI) was used as an indicator to investigate the impact of goggle-related heat strain on the ocular surface. Methods The basic functions of antifog, anti-ultraviolet (UV), and anti-blue-light radiation capabilities were evaluated. Furthermore, the clinical impact on noninvasive keratography tear film break-up time (NIKBUT), intraocular pressure, central corneal thickness, Schirmer test I, and the Dry Eye-related Quality of life Score (DEQS) were assessed in 40 healthcare workers by comparing MG with standard goggles (SG). The relationships between THI and the above parameters were explored. Results MG had a significantly longer antifog time than SG (212.75 ± 23.95 vs. 138.35 ± 5.54 min, p < 0.05), stronger antiultraviolet ability at 400 nm (99.99 vs. 45.55%), and optimal anti-blue-light performance at 440 nm (33.32 vs. 13.31%). Tear film stability after wearing the goggle was significantly worse than that before wearing them (p < 0.05). Both goggles achieved moderate to strong heat strain, with a THI of >80 at all timepoints. The MG group showed lower THI and DEQS and higher NIKBUT than the SG group (p < 0.05). THI was significantly correlated with DEQS, NIKBUT, and real fogging time (r = 0.876, −0.532, −0.406; all p < 0.05). Conclusion Wearing goggles for a long time may cause heat strain to the eyes, thereby leading to eye discomfort and changes in the microenvironment of the ocular surface. Our MG exhibited better antifog, antiultraviolet, and optimal anti-blue-light performance and lower heat strain than SG, thus making it ideally suited for healthcare workers.